Aktivitas Antibakteri Ekstrak Etil Asetat Kulit Biji Lamtoro (Leucaena leucocephala) terhadap Bakteri Propionibacterium acnes: Aktivitas Antibakteri Ekstrak Etil Asetat Kulit Biji Lamtoro (Leucaena leucocephala) terhadap Bakteri Propionibacterium acnes - Bulu, Atalia Tamo Ina; Shalsabilla, Lulu; Solichah, Ayu Ina (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Acne is an inflammation that is accompanied by blockage of the ducts of the skin’s oil glands (sebum) and hair (pilosebaceous ducts). Propionibacterium acnes is one of the bacteria that contribute to acne. Some natural ingredients such as lamtoro seed husk have flavonoids, alkaloids, saponins, and tannins which are antibacterial compounds that inhibit the growth of Propionibacterium acnes. This study aims to determine the antibacterial activity of ethyl acetate extract from lamtoro seed husk which is effective in inhibiting the growth of Propionibacterium acnes. Lamtoro seed husk (Leucaena leucocephala) was extracted by remaceration method using ethyl acetate solvent. Phytochemical identification is done qualitatively through color reaction with appropriate reagents confirmed by the TLC test. The results of the analysis showed that ethyl acetate extract of lamtoro seed husk had antibacterial activity against the growth of Propionibacterium acnes bacteria with the average diameter of the inhibition zone in the 15%, 20%, and 25% extract concentrations series of 1,454 mm, 3,313 mm, and 5,763 mm. Based on this study, it can be concluded that there is an influence of the concentration of ethyl acetate extract of lamtoro seed husk on the antibacterial activity of Propionibacterium acnes, the greater the concentration of the extract, the greater the diameter of the inhibition zone.